DANGEROUS INFORMATION ATTACKS THAT HAVE A NEGATIVE IMPACT ON HUMANITY'S LIFE (Academicia Globe: Inderscience Research, 2023)
This article details the development of information technologies and telecommunications in high pictures and their danger to society, the damage that occurs after information attacks and the problems of each state in ensuring its information security.